2019
DOI: 10.1111/and.13455
|View full text |Cite
|
Sign up to set email alerts
|

Effect of recombinant β‐defensin 1 protein on human sperm motility and viability

Abstract: The reduction of sperm motility and subsequently reduced ability to undergo capacitation and acrosome reaction are considered as common causes of male infertility. The β‐defensin family is a group of well‐known secretory proteins with antimicrobial activity that contribute to the process of “sperm maturation” during the passage of spermatozoa in the epididymis when spermatozoa attain its motility. One member of this family is “β‐defensin 1” which is present in seminal plasma and spermatozoa. The aim of this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…BDs) improve fertilization potential of sperm [71][72][73]. The addition of prokaryotically expressed bovine r-BBD126 protein to non-motile caput-epididymal spermatozoa improves their motility and mucus penetration ability but lacks the ability to improve fertility [74][75]. This failure to improve sperm fertilizing ability could be due to prokaryotic expression of bovine BBD126 because prokaryotes lack post-translational modi cation system and DEFB126 or its orthologs are known for their post-translational modi cations (glycosylations) [23,71].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…BDs) improve fertilization potential of sperm [71][72][73]. The addition of prokaryotically expressed bovine r-BBD126 protein to non-motile caput-epididymal spermatozoa improves their motility and mucus penetration ability but lacks the ability to improve fertility [74][75]. This failure to improve sperm fertilizing ability could be due to prokaryotic expression of bovine BBD126 because prokaryotes lack post-translational modi cation system and DEFB126 or its orthologs are known for their post-translational modi cations (glycosylations) [23,71].…”
Section: Discussionmentioning
confidence: 99%
“…The non-synonymous mutations (CC/AA and CT/AC) genotypes of cattle BNBD4 and DEFB103 are associated with higher milk, fat, proteins, lactose, dry matter contents, somatic cell counts, and resistance to mastitis [72,75,[83][84]. The genotypic analysis found that the human DEFB126 gene is highly polymorphic bearing 77 known SNPs, out of these, rs140685149 and rs11467497 are associated with human infertility affecting sperm surface glycans, motility (rs11467497), higher round cells in semen, cervical mucus penetration ability [10-11, 33-34, 74].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BDs) improve fertilization potential of sperm [71][72][73]. The addition of prokaryotically expressed bovine r-BBD126 protein to non-motile caputepididymal spermatozoa improves their motility and mucus penetration ability but lacks the ability to improve fertility [74][75]. This failure to improve sperm fertilizing ability could be due to the prokaryotic expression of bovine BBD126 because prokaryotes lack a post-translational modi cation system and DEFB126 or its orthologs are known for their post-translational modi cations (glycosylations) [23,71].…”
Section: The Possible Impact Of Nssnps On Bbd129 Protein Biological Functionsmentioning
confidence: 99%
“…In the bovine, studies are largely focused on genomic SNPs associated with milk production, susceptibility to immune function, and parasite resistance [82]. The non-synonymous mutations (CC/AA and CT/AC) genotypes of cattle BNBD4 and DEFB103 are associated with higher milk, fat, proteins, lactose, dry matter contents, somatic cell counts, and resistance to mastitis [72,75,[83][84].…”
Section: The Possible Impact Of Nssnps On Bbd129 Protein Biological Functionsmentioning
confidence: 99%